(untitled) - Botkin, James W. (Oxford, 1988)
This book reconsiders global problems such as energy and the arms race, as well as more recent issues like cultural identity, communications and information. Attention is primarily focused on human problems and potential, rather than on material constraints to growth. The analysis places particular importance on new forms of learning and education, for individuals and especially for society, as indispensable for laying the groundwork to deal with global issues, and for bridging the gap between the complexity and risks of current global issues and our presently inadequately developed capacity to face up to them. This is the first Club of Rome report to authors from socialist and Third World countries as well as from the West...
Keywords: Social change,Xã hội thay đổi